2013
DOI: 10.1007/s11664-013-2850-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Nano/microstructured p-Type Bi0.4Sb1.6Te3 Powders Fabricated by Mechanical Alloying and Vacuum Hot Pressing

Abstract: Two kinds of Bi 0.4 Sb 1.6 Te 3 powder with different particle and grain sizes were fabricated by high-energy ball milling. Powder mixtures with varied weight ratios were consolidated by vacuum hot pressing (HP) to produce nano/ microstructured composites of identical chemical composition. From measurements of the Seebeck coefficient, electrical resistivity, and thermal conductivity of these composites, a figure of merit (ZT) value of up to 1.19 was achieved at 373 K for the sample containing 40% nanograin pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The introduction of highly dense nano/micro-structured Bi 2 Te 3 nanocrystals is believed to provide fast carrier transport and improved electrical performance. 40–43 As shown in Fig. 1f, the Bi 2 Te 3 @PEDOT NW composite exhibits a sandwich-like assembled structure with a clear and tightly bonded interface between highly ordered stacked Bi 2 Te 3 nanocrystals and the nanoporous PEDOT NW scaffold (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The introduction of highly dense nano/micro-structured Bi 2 Te 3 nanocrystals is believed to provide fast carrier transport and improved electrical performance. 40–43 As shown in Fig. 1f, the Bi 2 Te 3 @PEDOT NW composite exhibits a sandwich-like assembled structure with a clear and tightly bonded interface between highly ordered stacked Bi 2 Te 3 nanocrystals and the nanoporous PEDOT NW scaffold (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…PbTe, Bi2Te3), Si-Ge alloys, rare earth chalcogenides and half-Heusler alloys [35][36][37][38]. It is also becoming more usual the enhancement of thermoelectric properties through doping [39,40], alloying [41,42] and material nanostructuring [43,44].…”
Section: Materials and Main Materials Propertiesmentioning
confidence: 99%
“…Over the past 30 years, various alloys idealized around bismuth telluride have been researched and optimized for TE applications [6]. Recent studies have shown that high performing p-type Bi0.4Sb1.6Te3 materials have been manufactured via mechanical alloying (MA) and hot extrusion in the temperature range of 360°C -450°C.…”
Section: Introductionmentioning
confidence: 99%